(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2024)
Productive employment is the foundation of a healthy economy and society. This not only creates jobs, but also ensures that workers earn a living wage while contributing to economic growth. This article explores the key aspects of productive employment, its impact on individuals and society, and strategies for expanding this type of employment. This study examines the empirical and conceptual research on the issues of productive employment and poverty reduction reflected in scientific sources in a number of online databases and systematizes the scientific approaches in them. As a scientific result of the research, a mechanism for ensuring productive employment of the country’s population was proposed.